Integrating Intercultural Values in English Reading Materials for Jayapura High School Students - Rachman, Putri Fitriastuty Indah Yasinta; Jamilah, Jamilah (Makassar State University, 2025)
Abstract. This research aims to develop supplementary reading materials for 10th-grade high school students in Jayapura, Papua. It is designed to help students understand English texts while introducing international, national (Indonesian), and local (Papuan) cultures. The study uses the research and development (R&D) model with the ADDIE approach. The needs analysis involved 220 students, followed by small group trials with 22 students and field trials with 65 students. Data were collected through questionnaires and interviews and analyzed using quantitative and qualitative methods. The results show that the developed materials meet students' needs, which were identified through a needs analysis focusing on students' reading difficulties, interests, and cultural exposure. The materials address these needs by incorporating culturally relevant content and interactive exercises. Additionally, they help improve students' reading comprehension through various strategies, such as text-based questions, vocabulary-building exercises, and pronunciation practice. The materials feature texts of 300–400 words, 30–40 new vocabulary words, vocabulary lists, and engaging images. Topics include historical sites, traditional foods, art, and customs. The implementation phase received positive feedback from students, teachers, and subject matter experts with an overall rating of 3.25 and 4.00, which is